STUDY OF CATALYTIC ACTIVITY AT DIFFERENT TEMPERATURES Ti02 IN A SAMPLE OF TEXTILE PIGMENT YELLOW 50 - Cesare C., Mary (2003)
In this paper the measurement of the activity of the catalyst type Ti02 anataza to different experimental conditions, in a display of yellow textile pigment yellow 50, pyrex used as glass reactor was performed , performing the following tests: 1) bubbling oxygen without the presence of catalyst exposed to ultraviolet light at room 2 temperature ) bubbling oxygen with catalyst and the presence of ultraviolet light at different temperatures , the results from these tests are compared , and a higher activity was obtained when the samples were sparged with oxygen and irradiated with UV lamp , visible and heated to 338 K. this pigment demineralization by measuring the UV - visible concentrations was found . The catalyst , titanium oxide ( Ti02 ) anataza type was characterized by the method of X-ray diffraction